The locus of control and sense of coherence and coping stress strategies at women of cancer patients of breast - Terelak, Jan Felicjan; Krzesicka, Elżbieta; Małkiewicz, Monika (Studia Psychologica: Theoria et praxis, 2009)
Work has empirical character and locus of control and sense of coherence concerns with preferred strategies relationships advice me with women’s stress with crayfish of breast. It advices to measurement of practical strategies me with stress were used was The Ways of Copying Questionnaire (WCQ) S. Folkman and R. Lazarus. Do it examining locus of control was used I-E Scale R.B. Rottera and the sense of coherence to measurement were used SOC - 29 A. Antonovsky. 64 women in investigation the relating modificatory part locus of control in report the control to strategy advice me with stress took the part, in age 34-73 years with different level of education and the recognition of tumour of chest gland as well as the healthy womens supervisory group. 50 sick’s women in investigation the relating modificatory part of sense of coherence in report to strategy advice me with stress took part on tumour of breast in age 20-60 years from average even 43,68 years with different level education as well as group supervisory healthy women. It was affirmed that the locus of control and sense of coherence have with strategies relationship advice me with stress. The ill women on crayfish of breast more often, than the healthy women, the strategies of advice apply me to be well - versed in emotionally and avoidance.